Table of Contents - Board, Editorial (Law, State and Telecommunications Review, 2022)
We are delighted to include articles on the benefits of e-services for both government and citizens in Mexico, the use of digital currencies in economic crimes in the absence of regulations in Ukraine, the inequalities concerning ethnic minority groups and online education during the COVID-19 Pandemic in Vietnam, the prospects of introducing the digital ruble within the territory of the Russian Federation, the threats and challenges for security measures on the Internet of Things (IoT), the usage of electronic transactions as evidences in court proceedings in Kazakistan, the possibilities of alternative dispute resolution mechanisms in digital transactions in Spain, the legal relation between the right of hearings and the media, and the processing of personal data in digital health applications in the COVID-19 Pandemic, both in the Colombian context.